Frailty and Emergency Surgery: Results of a Systematic Review and Meta-Analysis - Leiner, Tamas; Nemeth, David; Hegyi, Peter; Ocskay, Klementina; Virag, Marcell; Kiss, Szabolcs; Rottler, Mate; Vajda, Matyas; Varadi, Alex; Molnar, Zsolt (Frontiers in Medicine, 2022)
Background: Frailty, a “syndrome of loss of reserves”, is a decade old concept. Initially it was used mainly in geriatrics but lately its use has been extended into other specialties including surgery. Our main objective was to examine the association between frailty and mortality, between frailty and length of hospital stay (LOS) and frailty and readmission within 30 days in the emergency surgical population. Methods: Studies reporting on frailty in the emergency surgical population were eligible. MEDLINE (via PubMed), EMBASE, Scopus, CENTRAL, and Web of Science were searched with terms related to acute surgery and frail*. We searched for eligible articles without any restrictions on the 2nd of November 2020. Odds ratios (OR) and weighted mean differences (WMD) were calculated with 95% confidence intervals (CI), using a random effect model. Risk of bias assessment was performed according to the recommendations of the Cochrane Collaboration. As the finally selected studies were either prospective or retrospective cohorts, the “Quality In Prognosis Studies” (QUIPS) tool was used. Results: At the end of the selection process 21 eligible studies with total 562.070 participants from 8 countries were included in the qualitative and the quantitative synthesis. Patients living with frailty have higher chance of dying within 30 days after an emergency surgical admission (OR: 1.99; CI: 1.76-2.21; p<0.001). We found a tendency of increased LOS with frailty in acute surgical patients (WMD: 4.75 days; CI: 1.79-7.71; p=0.002). Patients living with frailty have increased chance of 30-day readmission after discharge (OR: 1.36; CI: 1.06-1.75; p=0,015). Conclusions: Although there is good evidence that living with frailty increases the chance of unfavourable outcomes, further research needs to be done to assess the benefits and costs of frailty screening for emergency surgical patients. Disclosure of funding: This work was supported by the Hungarian National Research, Development and Innovation Office (Grant No: K 138816). Registration: The review protocol was registered on the PROSPERO International Prospective Register of Systematic Reviews (CRD42021224689).